Double systemic cytokine release syndrome following sequential infusion of anti-CD22 and anti-CD19 chimeric antigen receptor T cells after autologous hematopoietic stem cell transplantation for a central diffuse large B-cell lymphoma patient: A case report and literature review - Zheng, Jing; Xiao, Yao; Wu, Xue Q.; Xiao, Qiong Z.; Feng, Chun; Gao, Kai B. (Frontiers in Immunology, 2023)
Background Chimeric Antigen Receptor T cell(CAR T-cell) therapy has been a great success in relapsed/refractory acute B lymphoblastic leukemia and B-cell lymphoma. At the same time, there are also related adverse reactions, especially cytokine release syndrome(CRS) and immune effector cell associated neurotoxicity syndrome(ICANS). However, Double CRS caused by CRA T cells are very rare. Case Report Here, we report a 33-year-male with secondary central diffuse large B-cell lymphoma(CNSL) who develpoed double CRS following sequential infusion of Anti-CD22 and Anti-CD19 CAR T cells after autologous hematopoietic stem cell transplantation(ASCT). On the second day after CAR T-cell infusion, the patient developed high fever, along with chilly sensation, shivering, headache, blood oxygen desaturation, shock, weakness, severe thirst, and heart rate decline. IL-6 and ferritin increased significantly. The patient was diagnosed with the first CRS (grade 3). On the 33th day, the patient again had a persistent fever(T>39℃) and limbs rash. IL-6 and ferritin again increased significantly on the 35th day. After exclusion of infection, a diagnosis of double CRS was made. The patient’s symptoms were completely relieved after receiving tocilizumab, glucocorticoids, and other supportive treatments. Conclusion This is the first reported case worldwide where the patient with secondary CNSL suffered double CRS after CAR T-cell infusion. Our findings showed that it is important to increase awareness of early detection and diagnosis of double CRS and adopt appropriate treatment strategies.